A novel pathway for mineralization of the thiocarbamate herbicide molinate by a defined bacterial mixed culture - Barreiros, Luísa (2011)
A bacterial mixed culture able to mineralize molinate as established, through enrichment, using mineral medium with molinate as the only carbon, nitrogen and energy source. The combination of five cultivable isolates, purified from the enrichment culture, permitted the reconstitution of a degrading consortium. Both enrichment and defined cultures were able to mineralize molinate without accumulation of degradation products by the end of the growth. Among the five isolates constituting the defined mixed culture, an actinomycete, strain ON4, was essential for biodegradation, being involved in the cleavage of the thioester bond of molinate, the initial step of the degradation pathway. Isolate ON4 was able to grow on molinate at concentrations below 2 mM, with the accumulation of ethanethiol and diethyl disulphide. These sulphur compounds were toxic to strain ON4 when accumulating at higher concentrations. However, this inhibitory effect was avoided by the presence of other members of the mixed culture, out of which isolates ON1 and ON2 were observed to consume ethanethiol and diethyl disulphide. In this way, interactions among defined mixed culture members involve metabolic and detoxifying association